Regional network governance and sustainable tourism - Farmaki, Anna (My University, 2015)
Effective governance has been identified as one of the most important factors in sustainable tourism implementation. As governance structures are increasingly becoming network-based, attention needs to be diverted to the effectiveness of partnerships in achieving sustainability in tourism. Evaluating the effectiveness of regional tourism governance in Cyprus by considering regional tourism organisations’ (RTOs) public–private network involved exploratory research whereby semi-structured interviews with key tourism stakeholders were performed. Findings reveal that network governance-related challenges interact with region-specific characteristics, inhibiting the effectiveness of regional tourism governance in implementing sustainable tourism. Specifically, RTOs represent a weak form of governance and their effectiveness in implementing sustainable tourism is limited by the continuing dependence on foreign tour operators, a system of mutual favours which complexifies the nature of tourism planning and a growing emphasis on economic interests further fuelled by recent austerity measures imposed in Cyprus. The paper concludes that network governance cannot be considered separately from the socio-cultural, economic and environmental factors of the context in which it is studied and proposes that further research reflects the horizontal relations across regional, national and global networks.
Keywords: Cyprus; Governancepublic–private networks; Regional tourism; Sustainable tourism; Tourism planning